Task, muscle and frequency dependent vestibular control of posture - Forbes, Patrick A.; Siegmund, Gunter P.; Schouten, Alfred C.; Blouin, Jean-Sébastien (Frontiers in Integrative Neuroscience, 2015)
The vestibular system is crucial for postural control; however there are considerable differences in the task dependence and frequency response of vestibular reflexes in appendicular and axial muscles. For example, vestibular reflexes are only evoked in appendicular muscles when vestibular information is relevant to postural control, while in neck muscles they are maintained regardless of the requirement to maintain head on trunk balance. Recent investigations have also shown that the bandwidth of vestibular input on neck muscles is much broader than appendicular muscles (up to a factor of 3). This result challenges the notion that vestibular reflexes only contribute to postural control across the behavioral and physiological frequency range of the vestibular organ (i.e., 0-20 Hz). In this review, we explore and integrate these task-, muscle- and frequency-related differences in the vestibular system’s contribution to posture, and propose that the human nervous system has adapted vestibular signals to match the mechanical properties of the system that each group of muscles controls.